2017
DOI: 10.5713/ajas.16.0987
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth performance of Berkshire purebreds and crossbreds sired by Hereford and Tamworth breeds raised in alternative production system

Abstract: ObjectiveThe objective of the present study was to compare growth performance of Berkshire purebred pigs (BB), Hereford (HB) and/or Tamworth (TB) sired Berkshire crossbred pigs reared in a hoop structure in two experiments.MethodsIn the first experiment, BB was compared to TB while HB and TB were compared in the second. Body weights (BW) were recorded at 3 days of age and every 28 days from birth until 140 days of age. There was no significant difference between the BW of BB and TB, but HB was heavier than TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The biological patterns of growth have been thoroughly studied as exemplified by Shull, 6 Park et al, 7 and Park and Oh 8 . An average growing pattern under relatively normal circumstances can establish the time required for hogs and pigs to reach a weight of 250 lbs, which is approximately the weight threshold that makes a hog ready to be processed by slaughter facilities 9 .…”
Section: Sources Of Informationmentioning
confidence: 99%
“…The biological patterns of growth have been thoroughly studied as exemplified by Shull, 6 Park et al, 7 and Park and Oh 8 . An average growing pattern under relatively normal circumstances can establish the time required for hogs and pigs to reach a weight of 250 lbs, which is approximately the weight threshold that makes a hog ready to be processed by slaughter facilities 9 .…”
Section: Sources Of Informationmentioning
confidence: 99%
“…Crossbreeding between Duroc and Polish Landrace sheep can improve tenderness ( 1 ), and hybrid Berkshire × QingYu pigs exhibited improved carcass quality, with a significant increase in lean percentage and reduced sebum percentage ( 2 ). Sang et al showed that heterosis from crossbreeding can yield high meat quality ( 3 ). Southdown and Suffolk are specialized for meat production and exhibit early growth and excellent meat quality; these sheep are recognized as the most popular breeds for meat production ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%